One Conservation concept in practice - Thiago Cavalheri Luczinski; Pedro Nacib Jorge-Neto; Rafaella Martins Ribeiro; Rogério Silva de Jesus; Cristiane Schilbach Pizzutto; Thyara de Deco-Souza; Gediendson Ribeiro de Araújo; Thais Oliveira Morgado; Sandra Helena Ramiro Corrêa; Maurício A.S. Peixer; Patricia Furtado Malard; Gabriele Bortolotto; et al. (Theriogenology Wild, 2023)
The One Conservation is an integrative process for biodiversity conservation. This communication describes how this integrated method, involving many institutions, resulted in the birth of a jaguar cub that should be reintroduced to the wild, thereby contributing to the species' long-term survival. Each parent was saved from the wilderness. While the sire was saved as a cub, the dam was rescued after the devastating Pantanal wildfires that killed over 16.9 million vertebrates. Rescues, treatments, and ex situ care involved a large number of specialists and institutions. We report the ex situ reproduction of the only pair of Jaguars under reproductive age from the Pantanal biome. The One Conservation approach made the good outcome possible, which brought together numerous people and organizations.